Consumptionscape of Turkish Feminist Mothers: Negotiations between Motherhood, Consumer Culture and Feminist Ideologies - Miray Baybars; Ayla Özhan-Dedeoğlu (Istanbul Business Research (IBR), 2021)
The present study analyzes consumption practices of feminist mothers and how they negotiate tensions arising from the clash of their multiple identities and marketplace behaviors. Having a broad research focus, this study aims to contribute to the epistemic terrain of motherhood and consumption and provide new theoretical explanations by revealing the extent of negotiations at the crossing axes of consumer, feminist and mother roles. The findings reveal that feminist mothers negotiate different cognitions, practices and narratives of identity, and develop a practical logic based on the interplay between authentic and mass-produced, natural and artificial, branded and generic, traditional and modern, industrial and rural, over-consumption and needs-satisfaction without necessarily privileging one over the other. The present study fills a theoretical gap by revealing how their practices incorporate a polysemous quality based on their intertwined roles and discourses.
Keywords: 650; Feminist Mothers; Motherhood; Consumption; Negotiations